Special performance of young soccer players with Grudziadz Sports Club Olympia longitudinal in the light of research - Marks, Adam; Napierała, Marek; Gotowski, Rafał (Journal of Education, Health and Sport, 2016)
The aim of the study was to evaluate the efficiency of special young players Grudziądz Sports Club GKS Olimpia in longitudinal studies. By means of special fitness tests were evaluated four times the level of football technique and motor skills like speed, endurance and coordination. It was also examined the level of somatic development players, particularly height and weight. Conclusions: (1) Among the motor skills of young players the best developed endurance and strength, the least the maneuverability and speed, (2) In the analyzed period was a marked improvement technical skills.